The Influence of Hoax News on Social Media on Netizens' Social Concern in the Cianjur Earthquake Disaster - Ziyah, Siti Faoziyah Alawiyah; Aryani, Dwi; Sardin, Sardin; Kurniati, Erisa; John, Yeo Wee (Jurnal Sains Sosio Humaniora, 2025)
In the digital era, freedom of speech on social media is often misused to spread hoax news, which is inaccurate information that aims to mislead the public and trigger division. One of the cases widely discussed is the hoax related to the rejection of aid by victims of the Cianjur earthquake, which triggered misunderstandings among netizens. This study aims to analyze the influence of hoax news on social media on netizens' social concern for the disaster. The method used is quantitative, with primary and secondary data and simple linear regression analysis to measure the relationship between variable X (hoax news) and variable Y (social concern). This study involved 40 respondents from various backgrounds: students, college students, workers, and housewives. The results show that hoax news affects netizens' social concerns, with a contribution of 33.4% and a correlation of 0.578. These findings prove that hoax news can influence a person's mindset, actions, and social concerns, potentially threatening community life. Hopefully, this study will broaden horizons and encourage netizens to be more critical in receiving information.